PENGARUH BI RATE TERHADAP PASAR UANG DAN PASAR MODAL DI INDONESIA - B01108019, Nurlaily J. Handayani (Jurnal Pembangunan dan Pemerataan, 2012)
Title of the thesis is The Effect of BI Rate Against Money Market and Capital Market in Indonesia. The purpose of this study was to analyze the effect of the BI Rate of Interest Rate Interbank Money Market in Indonesia and the effect of the BI Rate to Composite Stock Price Index in Indonesia. This study uses quantitative methods, namely the processing of secondary data which is then carried out an analysis of the research object in accordance with the objectives of the study. The data used are secondary data in the form of monthly data published 2006.1-2011.12-year periode from the publication of Bank Indonesia (Bank Indonesias annual report, SEKI, SEMI), BPS, BAPPEPAM, and other sources. From the research results can be seen that BI Rate has a positive and significant impact on interbank rates at 95% confidence level, while the BI Rate has a significant negative effect on stock index and the 95% confidence level. Key words: BI Rate, Composite Stock Price Index, Interbank Interest Rate.